Cover Feature: Directing Polymorphism in the Helical Nanofilament Phase (Chem. Eur. J. 24/2021). Issue 24 (11th March 2021) - Park, Wongi; Yang, Minyong; Park, Hyewon; Wolska, Joanna M.; Ahn, Hyungju; Shin, Tae Joo; Pociecha, Damian; Gorecka, Ewa; Yoon, Dong Ki
Abstract : Polymorphism is defined as the formation of more than two kinds of crystal structures from a single compound, which is essential for practical applications such as pharmaceuticals and agriculture. Stimuli‐responsive polymorphism of the helical nanofilament (HNF) is investigated by using light‐driven and nanoconfinement methods. The light‐driven HNFs form the twisted ribbons, while the nanoconfined HNFs show the cylindrical ribbons. The discovery of polymorphism on HNF structures will provide insights for future studies on chirality. More information can be found in the Full Paper by D. K. Yoon et al. on page 7108 .